Effect of transfusion of fresh frozen plasma on parameters of endothelial condition and inflammatory status in non-bleeding critically ill patients: a prospective substudy of a randomized trial - Straat, Marleen; Müller, Marcella CA; Meijers, Joost CM; Arbous, Mendi S; Spoelstra - de Man, Angelique ME; Beurskens, Charlotte JP; Vroom, Margreeth B; Juffermans, Nicole P (Critical care (London, England), 2015)
Introduction Much controversy exists on the effect of a fresh frozen plasma (FFP) transfusion on systemic inflammation and endothelial damage. Adverse effects of FFP have been well described, including acute lung injury. However, it is also suggested that a higher amount of FFP decreases mortality in trauma patients requiring a massive transfusion. Furthermore, FFP has an endothelial stabilizing effect in experimental models. We investigated the effect of fresh frozen plasma transfusion on systemic inflammation and endothelial condition. Methods A prospective predefined substudy of a randomized trial in coagulopathic non-bleeding critically ill patients receiving a prophylactic transfusion of FFP (12 ml/kg) prior to an invasive procedure. Levels of inflammatory cytokines and markers of endothelial condition were measured in paired samples of 33 patients before and after transfusion. The statistical tests used were paired t test or the Wilcoxon signed-rank test. Results At baseline, systemic cytokine levels were mildly elevated in critically ill patients. FFP transfusion resulted in a decrease of levels of TNF-α (from 11.3 to 2.3 pg/ml, P = 0.01). Other cytokines were not affected. FFP also resulted in a decrease in systemic syndecan-1 levels (from 675 to 565 pg/ml, P = 0.01) and a decrease in factor VIII levels (from 246 to 246%, P <0.01), suggestive of an improved endothelial condition. This was associated with an increase in ADAMTS13 levels (from 24 to 32%, P <0.01) and a concomitant decrease in von Willebrand factor (vWF) levels (from 474 to 423%, P <0.01). Conclusions A fixed dose of FFP transfusion in critically ill patients decreases syndecan-1 and factor VIII levels, suggesting a stabilized endothelial condition, possibly by increasing ADAMTS13, which is capable of cleaving vWF. Trial registrations Trialregister.nl NTR2262 , registered 26 March 2010 and Clinicaltrials.gov NCT01143909 , registered 14 June 2010.